Wanprestasi Dalam Perjanjian Kredit Perumahan Dilihat Dari Undang-Undang No.8 Tahun 1999 Tentang Perlindungan Konsumen - Siti Mirta Liyani Halid; Nirwan Junus; Moh Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine and analyze how the legal protection of consumers due to default in the housing loan agreement in the perspective of Consumer Protection Law No.8 of 1999. The type of research used in this study is normative juridical approach to legislation (statute aprouch) and case approach (case aprouch). The results of this study indicate that the case of default in the housing loan agreement, which occurred in the city of Gorontalo. Create legal protection against consumers (customers) who are harmed by Bank BTN who do not carry out their obligations in accordance with existing rules or regulations, where the bank does not issue housing certificates even though the consumer (customer) has paid the installments